2020
DOI: 10.1089/lgbt.2018.0230
|View full text |Cite
|
Sign up to set email alerts
|

Association of Enacted Stigma with Depressive Symptoms Among Gay and Bisexual Men Who Have Sex with Men: Baltimore, 2011 and 2014

Abstract: Purpose: We assessed differences between gay and bisexual men in enacted stigma, and how the association between stigma and depressive symptoms may vary according to sexual orientation identity. Methods: Participants (671 gay and 331 bisexual men who have sex with men) in Baltimore's 2011 and 2014 National HIV Behavioral Surveillance completed an anonymous survey, including 3 enacted stigma dimensions and the Center for Epidemiologic Studies Depression Scale. Adjusted prevalence ratios were calculated through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…We found significant positive associations between enacted and internalized sexual orientation stigma and depression and anxiety among the PrEP users, which has been found in other studies with GBM globally (Marti-Pastor et al, 2020; Newcomb & Mustanski, 2010). Given that internalized stigma may be caused by systematic stigma (at the level of institutions and policies), these findings indicate that there is a need for social support interventions coupled with multilevel stigma interventions to address stigma perpetration across multiple levels of socioecological framework (Nelson et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found significant positive associations between enacted and internalized sexual orientation stigma and depression and anxiety among the PrEP users, which has been found in other studies with GBM globally (Marti-Pastor et al, 2020; Newcomb & Mustanski, 2010). Given that internalized stigma may be caused by systematic stigma (at the level of institutions and policies), these findings indicate that there is a need for social support interventions coupled with multilevel stigma interventions to address stigma perpetration across multiple levels of socioecological framework (Nelson et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Globally, research has found that gay and bisexual individuals experience a higher prevalence of depression and anxiety compared to their heterosexual counterparts (Cochran et al, 2003; Ross et al, 2018). Among gay and bisexual men (GBM), sexual orientation stigma is one of the drivers of depressive symptoms and poor mental health (Marti-Pastor et al, 2020; McLaren, 2016; Wight et al, 2012; Yolaç & Meriç, 2021). Additionally, studies in the United States with GBM have found associations between depression and anxiety symptoms and sexual risk behaviors, including reduced condom use and increased sexual encounters (Millar et al, 2017; Parsons et al, 2003).…”
mentioning
confidence: 99%
“…These results are consistent with previous studies, which demonstrated that personal experiences of discrimination were associated with greater psychological distress, psychiatric diagnoses, and mental health care utilization among sexual minorities (Burgess et al, 2007). Marti‐Pastor et al (2020) found that cisgender sexual minority men who reported enacted stigma experiences presented a higher prevalence of clinically relevant depressive symptoms than those who reported not having any enacted stigma experiences. Findings from our study provide further evidence demonstrating that enacted stigma undermines the mental health and well‐being of cisgender men in same‐gender partnerships.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24] Stigma encompasses a complex set of labels or stereotypes and prejudices attributed to an individual's social or clinical conditions and limits access to health resources because of bias or discrimination. 23,[25][26][27][28][29] Of the frameworks and typologies used to describe stigma, 3 types are particularly relevant for OUD: 30 (1) origin stigmathe belief that an individual with a stigmatized condition acquired it because of avoidable actions that were under the control of the individual 31 ; (2) enacted stigma-practices of operationalizing labels and stereotypes as policies or patterns of behaviors that are directed at or perceived by those with a stigmatized phenotype [32][33][34][35][36][37][38][39] ; and (3) intersectional stigma-the presence of multiple stigmatizing conditions in people and their collective impact on health outcomes. [40][41][42] Understanding of how these types of stigma serve as barriers to care for people with OUD is in a nascent stage, particularly in primary care clinician training environments.…”
Section: Introductionmentioning
confidence: 99%